HAM analysis for MHD Williamson-Casson hybrid nanofluid flow across stretching/shrinking surface influenced by melting heat transfer variable viscosity and viscous dissipation - Rehman, Ali; Saad, Abdullah Aziz; İnç, Mustafa; Mohammad, Alsharef; Aly, Ayman A. (Wiley-V C H Verlag Gmbh, 2025)
The MHD flow of a Williamson-Casson hybrid nanofluid (HNF) above a stretching or contracting surface is examined in this work. It examines the impacts of viscous dissipation, melting heat transfer (HT), and changing viscosity. The controlling PDEs are transformed into a system of nonlinear ODEs by similarity transformations (STs). We provide semi-numerical solutions for temperature and velocity distributions using the homotopy analysis method (HAM). The effects of important physical parameters on the flow and thermal properties are examined. These include the magnetic field (MF) parameter, viscosity fluctuations, Williamson parameter, Casson parameter (nanoparticle volume friction), heat source/sink parameter (HSSP), and Eckert number (EN). The findings demonstrate that improving viscous dissipation and MF improves thermal energy transmission, and that varying viscosity significantly alters the velocity profile (VP). The study offers information on how to best optimize HT mechanisms in HNF-related industrial and biomedical applications.
Keywords: Stagnation-Point Flow; Vertical Flat-Plate; Sheet; Slip; Hall